Impact of cardiovascular comorbidities on COPD Assessment Test (CAT) and its responsiveness to pulmonary rehabilitation in patients with moderate to very severe COPD: protocol of the Chance study. Issue 7 (21st July 2015) - Smid, Dionne E; Wilke, Sarah; Jones, Paul W; Muris, Jean W M; Wouters, Emiel F M; Franssen, Frits M E; Spruit, Martijn A
Abstract : Introduction: Chronic obstructive pulmonary disease (COPD) is a major cause of morbidity and mortality. Patients with COPD are characterised by a reduced health status, which can be easily assessed by the COPD Assessment Test (CAT). Previous studies show that health status can be worsened by the presence of comorbidities. However, the impact of cardiovascular comorbidities on health status as assessed with CAT is not sufficiently investigated. Therefore, the current study has the following objectives: (1) to study the clinical, (patho)physiological and psychosocial determinants of the CAT, and impact of previously established and/or newly diagnosed cardiovascular comorbidities on health status in tertiary care patients with COPD; (2) to assess the effects of pulmonary rehabilitation on CAT scores in patients with COPD; (3) to develop reference values for the CAT in Dutch elderly patients without COPD; and (4) to validate the CAT in a broad sample of Dutch patients with COPD. Methods and analysis: The C OPD, H ealth status an d C omorbiditi e s (Chance) study is a monocentre study consisting of an observational cross-sectional part and a longitudinal part. Demographic and clinical characteristics will be assessed in primary care, secondary care and tertiary care patients with COPD, and in patients without COPD. To assess health status, the CAT, Clinical COPD Questionnaire (CCQ) and St George's Respiratory Questionnaire (SGRQ) will be used. The longitudinal part consists of a comprehensive pulmonary rehabilitation programme in 500 tertiary care patients. For the cross-sectional part of the study, 150 patients without COPD, 100 primary care patients and 100 secondary care patients will be assessed during a single home visit. Ethics and dissemination: The Medical Ethical Committee of the Maastricht University Medical Centre+ (MUMC+), Maastricht, the Netherlands (METC 11-3-070), has approved this study. The study has been registered at the Dutch Trial Register (NTR 3416).